Multiscale Methods for the Flow During Grinding - Crowson, Zakhary (2023)
When the machining process known as grinding is used, a grinding fluid is applied to regulate the temperature of the workpiece and reduce the risk of expensive thermal damage. The factors which influence the transport of this fluid are not well understood. However, they are important to understand otherwise unnecessary cost can be incurred from inefficient application of the grinding fluid.